Legalised non-consensual sterilisation – eugenics put into practice before 1945, and the aftermath. Part 2: Europe. (4th May 2018) - Amy, Jean-Jacques; Rowlands, Sam
Abstract: This article deals with the nine European nations which legalised non-consensual sterilisation during the interwar years, thus completing the review, the first part of which was published in an earlier issue of this Journal. Like we did for North America, Japan and Mexico, countries concerned are addressed in chronological order, as practices in one of these influenced policies in others, involved later. For each, we assess the continuum of events up to the present time. The Swiss canton of Vaud was the first political entity in Europe to introduce a law on compulsory sterilisation of people with intellectual disability, in 1928. Vaud's sterilisation Act aimed at safeguarding against the abusive performance of these procedures. The purpose of the laws enforced later in eight other European countries (all five Nordic countries; Germany and, after its annexation by the latter, Austria; Estonia) was, on the contrary, to effect the sterilisation of large numbers of people considered a burden to society. Between 1933 and 1939, from 36, 000 to 400, 000 residents (two-thirds of whom were women) were compulsorily sterilised in Nazi Germany. In Sweden, some 32, 000 sterilisations carried out between 1935 and 1975 were involuntary. It might have been expected that after the Second World War ended and Nazi legislation was suspended in Germany and Austria, including that regulating coerced sterilisation, these inhuman practices would have been discontinued in all nations concerned; but this happened only decades later. More time still went by before the authorities in certain countries officially acknowledged the human rights violations committed, issued apologies and developed reparation schemes for the victims' benefit.